2017
DOI: 10.1002/slct.201701137
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Calculations of Rate Constants for the Forward and Reverse H2O + CO ↔ HCOOH Reactions

Abstract: The forward and reverse H2O + CO ↔ HCOOH reactions were investigated using high‐level methodologies in order to provide accurate thermodynamic and kinetic data between 200 and 4000 K. Geometries of reactants, transition state (TS), and product were determined with the Coupled Cluster Theory including single and double excitations (CCSD) along with the cc‐pVTZ basis set, whereas associated vibrational frequencies, zero‐point energies, and thermal corrections were scaled to consider anharmonicity effects. Beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Calvert et al, 2000). Recent theoretical (Nguyen et al, 2015;Stone et al, 2018;Peltola et al, 2020) works suggest that the only reaction pathway of the bis-oxy radical important under tropospheric conditions is isomerisation to "hot" formic acid, followed by decomposition to either H 2 + CO 2 or H 2 O + CO, in agreement with experimental and theoretical work on acid pyrolysis experiments (Chang et al, 2007;Vichietti et al, 2017). Due to the large excess energy and its small size, very little of the hot acid is stabilised, with measured HCOOH yields from ethene ozonolysis < 5 % (Calvert et al, 2000) (and the latter may be due to bimolecular reactions of SCI rather than stabilisation of the hot acid).…”
Section: Ch 2 Oosupporting
confidence: 62%
See 1 more Smart Citation
“…Calvert et al, 2000). Recent theoretical (Nguyen et al, 2015;Stone et al, 2018;Peltola et al, 2020) works suggest that the only reaction pathway of the bis-oxy radical important under tropospheric conditions is isomerisation to "hot" formic acid, followed by decomposition to either H 2 + CO 2 or H 2 O + CO, in agreement with experimental and theoretical work on acid pyrolysis experiments (Chang et al, 2007;Vichietti et al, 2017). Due to the large excess energy and its small size, very little of the hot acid is stabilised, with measured HCOOH yields from ethene ozonolysis < 5 % (Calvert et al, 2000) (and the latter may be due to bimolecular reactions of SCI rather than stabilisation of the hot acid).…”
Section: Ch 2 Oosupporting
confidence: 62%
“…Nguyen et al, 2015;Pfeifle et al, 2018), while OH elimination from the hot formic acid formed in the 1,3 ring closure (see Sect. 4.2) is not competitive against formation of H 2 O + CO and H 2 + CO 2 , as also borne out by HCOOH pyrolysis experiments (Chang et al, 2007;Vichietti et al, 2017). The carbonyl hydroperoxide route thus resolves an apparent discrepancy between ethene ozonolysis experiments, which observe significant OH yields, and experiments (Stone et al, 2018) and theoretical work (Nguyen et al, 2015;Pfeifle et al, 2018), which indicate very little OH formation from CH 2 OO.…”
Section: Poz Ring Opening To a Biradicalmentioning
confidence: 76%
“…Calvert et al, 2000). Recent theoretical (Nguyen et al, 2015;Stone et al, 2018;Peltola et al, 2020) works suggest that the only reaction pathway of the bis-oxy radical important under tropospheric conditions is isomerisation to 'hot' formic acid, followed by decomposition to either H2 + CO2 or H2O + CO, in agreement with experimental and theoretical work on acid pyrolysis experiments (Chang et al, 2007;Vichietti et al, 2017). Due to the large excess energy and its small size, very little of the hot acid is stabilised, with measured HCOOH yields from ethene ozonolysis < 5% (Calvert et al, 2000) (and the latter may be due to bimolecular reactions of SCI rather than stabilisation of the hot acid).…”
Section: Ch2oosupporting
confidence: 62%
“…However, theory has shown that direct OH formation from CH2OO by a 1,3-H-migration involves too high a barrier (e.g. Nguyen et al, 2015;Pfeifle et al, 2018), while OH elimination from the hot formic acid formed in the 1,3-ring closure (see Section 4.2) is not competitive against formation of H2O + CO and H2 + CO2, as also borne out by HCOOH pyrolysis experiments (Chang et al, 2007;Vichietti et al, 2017). The carbonyl hydroperoxide route thus resolves an apparent discrepancy between ethene ozonolysis experiments, which observe significant OH yields, and experiments (Stone et al, 2018)…”
Section: Poz Ring Opening To a Biradicalmentioning
confidence: 94%
“…Formic acid, HCOOH, the simplest carboxylic acid, has received a great deal of attention in the literature. Early theoretical 7–11 and experimental 12–18 studies of formic acid identified two primary unimolecular decomposition pathways, decarboxylation (forming CO 2 and H 2 ) and dehydration (forming CO + H 2 O). Studies in the literature agree that dehydration is the dominant pathway, though the two processes have energy barrier heights differing by only a few kcal/mol.…”
Section: Introductionmentioning
confidence: 99%